Assessing the Recent Escalation of the Nagorno-Karabakh Conflict in the Context of Failed Negotiations and Changing Geopolitical Environment - Fataliyev, Murad (ADA University, 2021)
Understanding the occurrence of war or conflict has been an exciting task for researchers and scholars to analyze. The recent military conflict in the Caucasus region provides a new opportunity to investigate the causes of the war. Second Karabakh War, which started on September 27th, 2020, and continued for 44 days, causing the loss of lives of thousands on both sides where Azerbaijan fought for its internationally recognized territories. Azerbaijan gained control of its internationally recognized regions while Russian peacekeeping forces were deployed in the Nagorno-Karabakh region. The main issue that will be investigated in this research paper is about Azerbaijan`s decision to start liberating its illegally occupied territories at that specific time. The paper tried to answer the questions by interviewing experts in the field, conducting discourse analysis by looking at speeches and interviews provided by Armenian and Azerbaijani leaders, and a supportive statistical analysis taken from different organizations. Findings suggested that Second Karabakh War occurred in the context of failed negotiations which caused diplomatic pessimism in the Azerbaijani government. Azerbaijan decided to force Armenia into cooperation or meaningful compromise, so Baku continued to liberate regions until Armenia agreed to sign the document that would bring more benefits to Azerbaijan. Also, the role of Turkey in the region as a rising power was an encouraging factor that made Azerbaijan continue military campaigns to liberate its internationally recognized territories from occupation.
Keywords: Public and International Affairs; Nagorno-Karabakh conflict.; Nagorno-Karabakh War.; Second Karabakh War.